1997
DOI: 10.1016/s0886-3350(97)80179-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term astigmatic changes after clear corneal cataract surgery

Abstract: The 12 o'clock incision was associated with a statistically insignificant increase in AA 2 years postoperatively and the lateral incision, with a statistically significant decrease. We currently recommend routine use of clear corneal incisions in cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
2
5
0
1
Order By: Relevance
“…This reduction of the tunnel size by 1 mm led to an overall reduction of the surgically induced astigmatism by half; while the 4.1-mm incision resulted in 0.8 dpt and confirmed previous results [6, 12], the astigmatism after a 3.2-mm incision was only 0.4 dpt. These comparative studies are easier to analyze with patients having an initial spherical cornea, because the absolute postoperative astigmatism is identical to the surgically induced astigmatism (fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This reduction of the tunnel size by 1 mm led to an overall reduction of the surgically induced astigmatism by half; while the 4.1-mm incision resulted in 0.8 dpt and confirmed previous results [6, 12], the astigmatism after a 3.2-mm incision was only 0.4 dpt. These comparative studies are easier to analyze with patients having an initial spherical cornea, because the absolute postoperative astigmatism is identical to the surgically induced astigmatism (fig.…”
Section: Discussionsupporting
confidence: 90%
“…This may be because our patients had a relatively low preoperative astigmatism (0.85). The steeper the axis on the incision site, the more relaxing is the effect of a corneal incision [6, 12]. In case of astigmatism against the rule, only the postoperative polar value according to Naeser (AKP2) was significantly different for the two types of incisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ophthalmic literature estimates that the magnitude of surgically induced astigmatism (SIA) studied by vector analysis is around 0.44 D and 0.88 D, rising as the size of the incision increases. [7][8][9][10][11][12][13] When the axis of the SIA was studied, it was observed that temporal incisions induced 'with the rule' astigmatism. 8,10,11 In this study, we aim to show whether or not MICS generates less astigmatism than CP with temporal incision.…”
Section: Introductionmentioning
confidence: 99%